HUBUNGAN PENGUNAAN KONTRASEPSI 3 BULAN DMPA DENGAN KENAIKAN BERAT BADAN DI TPMB ANNI LISTIAWATI - Kusmira, Novita Dewi; Alfitri, Rosyidah; Retnaningsih, Reny (NHM PRESS, 2024)
Injectable birth control is the most widely used form of birth control. Injectable birth control contains the hormone progesterone or a combination of the hormone estrogen progesterone. The 3-month injectable contraceptive type DMPA (depo medroxy progesterone acetate) is highly effective but has several side effects. One of the side effects that can result from using injectable birth control is weight gain. Generally, the increase in body weight is not too large, varying between less than 1 kg - 5 kg in the first year of use. Objective: To determine the relationship between the use of 3 month DMPA injection contraception and weight gain at TPMB Anni Listiawati. Method: This research uses correlational analysis with a cross sectional design. The research population was 58 3-month DMPA contraceptive acceptors at TPMB Anni Listiawati Researchers used the Total Sampling technique with a sample size of 58 people. Results: The research showed that there was a significant relationship between the use of 3-month DMPA contraceptive contraceptives and the weight gain of injectable contraceptive acceptors. The results of the Chi-Square test obtained a p-value of 0.000 < 0.05, meaning that H1 was accepted, there was a relationship between the use of 3-month DMPA contraception and weight gain at TPMB Anni Listiawati, Lumajang City. Family planning acceptors are expected to pay more attention to its benefits, advantages and side effects of the contraception to be used. It is recommended that health workers be more active in providing health education to the public, especially to mothers who are prospective family planning acceptors about the types, benefits, advantages, disadvantages and side effects of contraception.